Rosa rugosa R2R3-MYB transcription factors RrMYB12 and RrMYB111 regulate the accumulation of flavonols and anthocyanins - Shi, Yufeng; Lu, Taoran; Lai, Sanyan; Li, Song; Zhang, Ling; Liu, Rong; Ouyang, Lin; Zhao, Xinxin; Jiang, Yuqin; Yan, Zhen; Zhang, Ju; Miao, Baohe (Frontiers in Plant Science, 2024)
Roses (Rosa rugosa) are a famous flower with high ornamental and economic value. But the petals of roses are usually pink and purple, which restricted its application in garden settings. Flavonols and anthocyanins are crucial secondary metabolites related to flower pigmentation in plants. While MYB transcription factors involved in the biosynthesis pathway of anthocyanins have been identified in roses, the functional characterization of the MYB transcription factor regulating flavonol synthesis in R. rugosa remains unexplored. In this study, we isolated and characterized the R2R3-MYB transcription factors RrMYB12 and RrMYB111 involved in regulation of the flavonol biosynthetic pathway from R. rugosa. The bioinformatics analysis indicated that both the RrMYB12 and RrMYB111 belong to the R2R3-MYB subgroup 7 family. qRT-PCR analysis showed that RrMYB12 and RrMYB111 were expressed at low levels in roots and flowers. And transactivation activity assay indicated that RrMYB12 and RrMYB111 were transcriptional activators. The overexpression of RrMYB12 and RrMYB111 in tobacco resulted in an elevation of flavonol levels and a reduction in anthocyanin levels in flowers due to the upregulation of structural genes involved in flavonol synthesis, while the biosynthesis genes for the anthocyanin pathway were significantly downregulated. The transient reporter assay demonstrated that RrMYB12 exhibited strong activation of the promoters of RrCHS and RrFLS in Nicotiana benthamiana leaves following transient transformation. Furthermore, it was observed that RrMYBs displayed binding specificity to the promoter region of CsFLS.The functional characterization of the flavonol synthesis regulatory factors RrMYB12 and RrMYB111 offers a deeper understanding of the regulatory mechanism governing flavonol biosynthesis in roses, while also presenting an effective tool for genetic manipulation aimed at creating new varieties.